2022
DOI: 10.3390/biomedicines10071541
|View full text |Cite
|
Sign up to set email alerts
|

3D Human Organoids: The Next “Viral” Model for the Molecular Basis of Infectious Diseases

Abstract: The COVID-19 pandemic has driven the scientific community to adopt an efficient and reliable model that could keep up with the infectious disease arms race. Coinciding with the pandemic, three dimensional (3D) human organoids technology has also gained traction in the field of infectious disease. An in vitro construct that can closely resemble the in vivo organ, organoid technology could bridge the gap between the traditional two-dimensional (2D) cell culture and animal models. By harnessing the multi-lineage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 165 publications
(251 reference statements)
0
6
0
Order By: Relevance
“…Organoids are generated using different techniques, as such there is no specific protocol on the generation of organoids that has been developed. The morphological development of organoids may be restricted by naturally produced ECMs like Matrigel due to batch-to-batch variability and the presence of animal-derived products [ 143 , 144 ].…”
Section: Limitations Of Organoid Applicationmentioning
confidence: 99%
“…Organoids are generated using different techniques, as such there is no specific protocol on the generation of organoids that has been developed. The morphological development of organoids may be restricted by naturally produced ECMs like Matrigel due to batch-to-batch variability and the presence of animal-derived products [ 143 , 144 ].…”
Section: Limitations Of Organoid Applicationmentioning
confidence: 99%
“…The main organoid models we have focused on are similar and include lung and brain organoids. The virus invasion mechanism is the most common focus in this field of research and has been the predominant focus of all previous reviews [ 23 , 24 , 26 ]. This review differs, however, for the following reasons: (1) we have summarised novel organoid models that have not been mentioned in previous reviews, such as the skin, salivary, and nasal organoid models; (2) we have summarised the limitations of the organoid models and the problems encountered in previous organoid cultures and have provided advice to help address these issues in future investigations; (3) we have described the applications of organoids in tracing the origins, mutations, and species specificity of SARS-CoV-2, thus providing a novel angle for SARS-CoV-2 studies; and (4) we have also discussed the different organoid culture methods and compared them to determine the most suitable culture environment.…”
Section: Low Degree Of Organ Systematisationmentioning
confidence: 99%
“…A brain organoid was also used for the study of prion diseases, where it showed immune responses and individualized pathology changes with prion challenging. In addition, changes in cellular metabolism and cytokine secretion were also observed [ 26 ]. Holthaus et al found that the cAMP/PKA signalling pathway was the main pathway involved in the damage of the intestinal epithelium barrier, as a result of infection by Giardia duodenalis [ 27 ].…”
Section: Brief Introduction To Organoidsmentioning
confidence: 99%
“…The recent development of organoids, self-organizing 3D structures grown from stem cells that recapitulate essential aspects of organ structure and function, provides robust models to study infections directly in fully differentiated human tissues 27 . Originally established for gastrointestinal tissue 28 , several models are now available, including bladder 29 , pancreas 30 , liver 31 as well as upper 32 and lower 33 airways.…”
Section: Introductionmentioning
confidence: 99%